IMPELENTATION OF MINISTERIAL INSTRUCTION NO. 1 OF 2023 CONCERNING HALAL AND CANTEEN CERTIFICATION IN THE MINISTRY OF RELIGION WORK UNIT ENVIRINMENT (ANALYSIS OF THE PTKIN CHANCELLOR’S POLICY IN NORTH SUMATERA) - Dinda Alfia Safitri; Muhammad Ramadhan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This paper aims to analyze the implementation of Ministerial Instruction No. 1 of 2023 concerning Halal Certification of Products and Canteens within the Ministry of Religious Affairs Work Unit, a case study of the policy of the Rector of State Islamic Religious Universities Se – North Sumatra. The research method used is empirical law research by looking at and observing the rules related to the implementation of the acceleration of canteen halal certification in the PTKIN campus environment throughout North Sumatra. The results showed that the rector's policy related to the Instruction of the Minister of Religious Affairs which appealed to coordinate the acceleration of halal certification of products and canteens in the campus environment until now has not been circulated The Rector's Certificate about every canteen business actor is required to have Halal Certification because this regulation is still relatively new, therefore the Rector still uses the old rules / policies by selling halal products in accordance with the agreed contract together with canteen business actors. It is hoped that the Rector's policy will not only become a legal instrument, but also as a guide and spur to carry out the instruction of the Minister of Religious Affairs No. 1 of 2023 effectively and ensure that Islamic values ​​are well maintained in the campus environment.